CDC42-interacting protein 4 promotes metastasis of nasopharyngeal carcinoma by mediating invadopodia formation and activating EGFR signaling. Issue 1 (December 2017) - Meng, Dong-Fang; Xie, Ping; Peng, Li-Xia; Sun, Rui; Luo, Dong-Hua; Chen, Qiu-Yan; Lv, Xing; Wang, Lin; Chen, Ming-Yuan; Mai, Hai-Qiang; Guo, Ling; Guo, Xiang; et al.
Abstract Background Nasopharyngeal carcinoma (NPC) is a common malignancy in Southern China and Southeast Asia. In this study, we investigated the functional and molecular mechanisms by which CDC42-interacting protein 4 (CIP4) influences NPC. Methods The expression levels of CIP4 were examined by Western blot, qRT-PCR or IHC. MTT assay was used to detect the proliferative rate of NPC cells. The invasive abilities were examined by matrigel and transwell assay. The metastatic abilities of NPC cells were revealed in BALB/c nude mice. Results We report that CIP4 is required for NPC cell motility and invasion. CIP4 promotes the activation of N-WASP that controls invadopodia formation and activates EGFR signaling, which induces downstream MMP2 (matrix metalloproteinase 2) upregulation. In addition, CIP4 could promote NPC metastasis by activating the EGFR pathway. In nude mouse models, distant metastasis was significantly inhibited in CIP4-silenced groups. High CIP4 expression is an independent adverse prognostic factor of overall survival (OS) and distant metastasis-free survival (DMFS). Conclusion We identify the critical role of CIP4 in metastasis of NPC which suggest that CIP4 may be a potential therapeutic target of NPC patients.